Epistemic Rights in the Era of Digital Disruption - Aslama Horowitz, Minna; Nieminen, Hannu; Lehtisaari, Katja; D'Arma, Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open-access volume argues that in a functioning democracy, citizens should be equally capable of making informed choices about matters of social importance. This includes citizens accessing all relevant information and knowledge necessary for informed will formation. In today's complex era of digital disruption, it is not enough to simply speak about communication or even digital rights. The starting point for this volume is the need for 'epistemic equality'. The contributors seek to showcase the history and diversity of current debates around communication and digital rights, as precursors for the need for epistemic rights; both as a theoretical concept and an empirically assessed benchmark. The book highlights scholarship via academic case studies from around the world to feature different issues and methodological approaches, as well as similarities in academic and policy challenges across the globe. The goal is to provide an overview of issues that depict challenges toepistemic rights, extract both academic and applied policy implications of different approaches, and end with a set of recommendations for advancing policy-relevant scholarship on epistemic rights. This volume is intended as the first holistic response to an urgent need to address epistemic rights of communication as a central public policy issue, as an academic analytical concept, as well as a central theme for informed public debate. This book is open-access, meaning you have free and unlimited access. Minna Aslama Horowitz is Docent at the University of Helsinki, Finland, a Fellow at the Media and Journalism Research Centre, UK, and St. John$1 (Bs University, New York, USA. Hannu Nieminen is Professor Emeritus of media and communications policy, at the University of Helsinki, Finland, and Professor of Communication, at Vytautas Magnus University, Lithuania. Currently, he is also Visiting Professor at the London School of Economics and Political Science,UK. Katja Lehtisaari is a Senior Lecturer in Journalism at Tampere University, Finland, and Docent at the University of Helsinki, Finland. Alessandro D'Arma is Reader in Media and Communication and Director of the CAMRI PhD Programme, University of Westminster, UK.s
Part I Foundations -- 1 Introduction: The Epistemic Turn -- 2 Why We Need Epistemic Rights -- Part II Concepts and Issues -- 3 On the Need to Revalue Old Radical Imaginaries to Assert Epistemic Media and Communication Rights Today -- 4 Epistemic Rights, Information Inequalities, and Public Policy -- 5 (Re-)casting Epistemic Rights as Human Rights: Conceptual Conundrums for the Council of Europe -- 6 Epistemic Rights and Digital Communications Policies: Collective Rights and Digital Citizenship -- 7 Public Service Media: From Epistemic Rights to Epistemic Justice -- Part III National and Regional Cases -- 8 Towards Feminist Futures in the Platform Economy: Four Stories from India -- 9 Epistemic Rights and Right to Information in Brazil and Mexico -- 10 Digital Authoritarianism and Epistemic Rights in the Global South: Unpacking Internet Shutdowns in Zimbabwe -- 11 Epistemic Violators: Disinformation in Central and Eastern Europe -- 12 Nordic Illusion and Challenges for Epistemic Rights in the Era of Digital Media -- 13 Right to Data Access in the Digital Era: The Case of China -- Part IV Implications -- 14 Conclusion: Ubiquitous Need for Epistemic Rights and the Way Forward.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Digital media; Human rights; Mass media -- Political aspects; Digital and New Media; Politics and Human Rights; Media Policy and Politics